Easterine Kire’s A Respectable Woman: A Feminist Study - Swain, Tamishra; Chauhan, Neha (Bodhi: An Interdisciplinary Journal, 2023)
Women’s position since time immemorial has been secondary, whether in Western or Eastern culture. Women are not only pushed to the margin in the cultural, social, or economic sphere but also in the literary sphere. With growing awareness, women asked for equal rights in every sphere of life, whether in political, social or cultural spaces. Considering the condition in the literary sphere, one can see how women’s voices are never raised, or even if raised, they are never heard. However, by writing about their own experiences, women can represent themselves in a more accurate way, make their presence felt and challenge the mainstream writings mostly written by men. This paper tries to analyse Easterine Kire’s A Respectable Woman from a feminist perspective.